Inhibition of enteropathogens adhesion to human enterocyte-like HT-29 cells by a dairy strain of Propionibacterium acidipropionici - Zarate, Gabriela del Valle (2016)
Adhesion to the host intestinal mucosa is considered relevant for orally delivered probiotics as it prolongs their persistence in the gut and their health promoting effects. Classical propionibacteria are microorganisms of interest due to their role as dairy starters as well as for their functions as probiotics. Propionibacterium acidipropionici Q4, is a dairy strain isolated from a Swiss-type cheese made in Argentina that displays probiotic potential. In the present work we assessed the ability of this strain to adhere to the human enterocyte-like HT-29 cell line and to counteract the adhesion of two common human enteropathogens, such as Escherichia coli C3 and Salmonella Enteritidis 90/390. The results were compared with those obtained with the well-known probiotic Lactobacillus rhamnosus GG. P. acidipropionici Q4 showed a high adhesion capacity, even higher than the reference strain L. rhamnosus GG (42.3±4.4% and 36.2±2.3%, respectively), whereas adhesion of enteropathogens was significantly lower (25.2±2.2% for E. coli and 21.0±3.4% for S. Enteritidis). Propionibacteria as well as lactobacilli were able to inhibit by exclusion and competition the adherence of E. coli C3 and S. Enteritidis 90/390 whereas only L. rhamnosus GG displaced S. Enteritidis from HT-29 intestinal cells. Inhibition of pathogens by propionibacteria was not exerted by antimicrobials or coaggregation but was mainly due to exclusion by cell surface components, such as proteins and carbohydrates. The relevance of cell surface proteins (CSP) for preventing pathogens infection was confirmed by their concentration dependent effect observed for both pathogens: 100 μg/ml of CSP inhibited E. coli attachment almost as untreated propionibacteria, whereas it partially inhibited the attachment of S. Enteritidis. Results suggest that P. acidipropionici Q4 could be considered for the development of propionibacteria containing functional foods helpful in counteracting enteropathogen infection.